2004
DOI: 10.1016/s0014-5793(04)00239-x
|View full text |Cite
|
Sign up to set email alerts
|

Coronalon: a powerful tool in plant stress physiology

Abstract: Coronalon, a synthetic 6-ethyl indanoyl isoleucine conjugate, has been designed as a highly active mimic of octadecanoid phytohormones that are involved in insect and disease resistance. The spectrum of biological activities that is a¡ected by coronalon was investigated in nine di¡erent plant systems speci¢cally responding to jasmonates and/or 12-oxo-phytodienoic acid. In all bioassays analyzed, coronalon demonstrated a general strong activity at low micromolar concentrations. The results obtained showed the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 36 publications
3
74
1
7
Order By: Relevance
“…For treatment of various accessions with coronalon, hydroponically grown plants were placed with their roots in glass beakers containing 30 mL of hydroponic medium with 33 mg mL 21 (100 mM) coronalon, 0.1% ethanol (Schuler et al, 2004). Treatment was performed for 30 h. For treatments of detached Arabidopsis leaves with coronalon or alamethicin, 16 leaves were cut off from soil-grown plants and transferred with their petioles into glass beakers filled with 10-mL aqueous solutions of 16.5 mg mL 21 (50 mM) coronalon, 0.1% ethanol or 10 mg mL 21 alamethicin, 0.1% ethanol.…”
Section: Plant Treatmentsmentioning
confidence: 99%
“…For treatment of various accessions with coronalon, hydroponically grown plants were placed with their roots in glass beakers containing 30 mL of hydroponic medium with 33 mg mL 21 (100 mM) coronalon, 0.1% ethanol (Schuler et al, 2004). Treatment was performed for 30 h. For treatments of detached Arabidopsis leaves with coronalon or alamethicin, 16 leaves were cut off from soil-grown plants and transferred with their petioles into glass beakers filled with 10-mL aqueous solutions of 16.5 mg mL 21 (50 mM) coronalon, 0.1% ethanol or 10 mg mL 21 alamethicin, 0.1% ethanol.…”
Section: Plant Treatmentsmentioning
confidence: 99%
“…Methyl jasmonate (MeJA), (Z,E)-methyl 3-oxo-2-(2-pentyl) cyclopentane acetate is a plant hormone formed via the octadecanoid pathway together with jasmonic acid (JA) [18]. JA and MeJA are formed in plants under various biotic stresses.…”
Section: Exogenous Elicitorsmentioning
confidence: 99%
“…MeJA is a catabolite of JA and both activate genes controlling the secondary metabolic pathways. Synthetic octa-decanoid phytohormone mimic compounds like coronalon (6-ethyl indanoyl isoleucine conjugate) are highly active elicitor compounds inducing similar responses in several plant species [18].…”
Section: Exogenous Elicitorsmentioning
confidence: 99%
“…Investigations have revealed that coronatine showed different physiological effects on different tissues (Kenyon and Turner, 1990), and it is plausible that it acts differently in monocotyledon and dicotyledon plants (Uppalàpati et al, 2005). Many reports have shown that coronatine mediates the stress response associated with pathogens and herbivory (Lauchli and Boland, 2003;Schüler et al, 2004), and it was suggested to mediate plant responses to environment stresses. Our previous study showed that coronatine alleviated salinity stress in cotton by improving the antioxidative defense system and DPPH-radical scavenging activity (Xie et al, 2008), but its effects on drought and osmotic stress is still unknown.…”
mentioning
confidence: 99%